Risk factors for hospital admission of Brazilian children with non-rotavirus diarrhoea: a case control-study - Ichihara, Maria Yury T. (2015)
Background: Rotavirus has been the leading cause of severe cases of acute diarrhoea (AD) among children world wide, however, in the same areas, a large reduction in AD related to rotavirus has been observed after the introduction of the rotavirus vaccine. In Brazil, where there is a high rotavirus vaccine coverage, AD caused by pathogens other than rotavirus is still a frequent cause of outpatient visits and hospitalizations among children under 5 years. Methods: A hospital-based case-control study enrolled children aged 4 to 24 months admitted to 10 hospitals from all five Brazilian Regions. Cases (n¼ 1178) were children admitted with diarrhoea who tested negative for rotavirus in a stool sample. Controls (n¼ 2515) were children admitted without diarrhoea, frequency matched to cases bysex and age group. We estimated odds ratios using logistic regression, in a hierarchical approach according to a previously defined conceptual framework. Population-attributable fractions (PAF) were estimated for each variable, each block and for all significant variables in the latter model adjusted. Results: The factors studied accounted for 41% of the non-rotavirus AD hospital admissions and the main risk factors included lack of adequate excreta disposal (PAF ¼12%), untreated drinking water (PAF ¼11%) and a history of previous hospitalization due to AD (PAF ¼ 21%). Low socio-economic conditions, no public water supply,crowding and low weight-for-age made smaller contributions. Conclusions: These findings further our knowledge of risk factors associated with severe AD in the post-rotavirus vaccination era. We recommend further increase in coverage of basic sanitation, improvements in water quality and furtherexpansion of primary healthcare coverage to reduce the occurrence of non-rotavirus severe diarrhoea and subsequent hospitalization of Brazilian children.